Do voluntary certification standards improve yields and wellbeing? Evidence from oil palm and cocoa smallholders in Ghana - Brako, D.E.; Asare, R.; Alexandros, G. (Informa UK Limited, 2021)
Cocoa and oil palm production are major agricultural activities in Ghana, contributing substantially to the national economy and rural livelihoods. Even though smallholders produce practically all cocoa and a large fraction of oil palm in Ghana, their production is currently characterized by low yields and negative environmental and socioeconomic outcomes. Different certification standards have been promoted to enhance oil palm and cocoa sustainability in Ghana. This paper assesses the impact of certification standards on farm yields and the wellbeing of oil palm and cocoa smallholders. We focus on two sites of Ghana using a combination of monetary and non-monetary wellbeing indicators and Propensity Score Matching (PSM). Through certification, oil palm and cocoa smallholders adopt sustainable production practices (albeit to different extents), with certification having a mostly significant positive effect on farm yields, income and multidimensional poverty for both types of crop smallholders. However, certified cocoa smallholders have a relatively lower income diversification, which increases their vulnerability to price and yield fluctuations. It is important to build farmer capacity with income diversification strategies, possibly through the certification training received and the re-investment of the economic gains obtained through premiums and yield gains.